Shrinking Trust in Growing China: A Trade-Off Between Fast Growth, Change and Institutionalized Cooperation?. Issue 3 (24th July 2021) - Dai, Shuanping; Elsner, Wolfram
Abstract: Emergence and growth, or deterioration, of general trust, endogenously depend on socio-economic transformations. This paper attempts to explain a shrinking general trust in China, against the background of its 'reform-opening up' phase, by means of repeated prisoners' dilemma games on networks. We find that the more anonymous large-scale interaction arenas for immigrants in the boom regions, where lack of new, more appropriate network structures for them to substitute their lost rural home networks, resulted in higher uncertainty, integration failure, and less trust and cooperation. The general increase of social and geographical distance may have driven China from an 'acquaintance society' to a 'stranger society' with a lower general trust and institutionalized cooperation. A network model that addresses the interaction 'deep structure' of the socio-economy then may provide a potential strategic option for China to recover earlier high general trust.